Analisis dan Perencanaan Sistem Drainase di Lingkungan Universitas Lampung(Studi Kasus Zona II : Fakultas Matematika dan Ilmu Pengetahuan Alam, Fakultas Kedokteran dan Fakultas Keguruan dan Ilmu Pendidikan) - Kusuma, Widi Teja; Purwadi, Ofik Taufik; Sumiharni, Sumiharni (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
Lampung University as one of the first and oldest universities in Lampung Province is one of the best universities in Sumatra and continues to improve its academic quality, and have A Accreditation. The improvement of Lampung University facilities and infrastructure is continuously conducted in order to improve both academic and non-academic quality. The form of non-academic quality improvement is environmental arrangement with the drainage system planning. It is intended to solve some of the flood puddles that occurred during the rainy season due to the lack of optimal condition of existing drainage in the University of Lampung.The analysis conducted in this research includes hydrological analysis and hydraulics analysis. Hydrological analysis aimed to calculate the discharge plan using rational method and hydraulic analysis aims to calculate the capacity of existing drainage channels. So we can know the position of the flood point and planning the new channel dimension.Based on the analysis of the flood point occurred at DN15 cross section with 9.5 m long overflow which is located in front of the entrance portal of Faculty of Mathematics and Sciences. There are also some new drainage section design at DN63 point along 56 m, DN64 along 45 m and DN65 along 67 m as they are still a natural drainage. It is also necessary to give the drainage channel maintenance by channel normalization, garbage retaining lattice installation, and periodic cleaning of channels.